Nonresonant third-order nonlinear properties of NaPO3-WO3-Bi2O3 glasses in the near infrared - dos Santos, F. E. P.; de Araujo, C. B.; Gomes, A. S. L.; Fedus, K.; Boudebs, G.; Manzani, D. [UNESP]; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2009)
nonlinear (NL) refractive index, n(2), of NaPO3-WO3-Bi2O3 glass with different relative amounts of the constituents was measured at 1064 and 800 nm using the Z-scan and the thermally managed eclipse Z-scan techniques, respectively. The values of n(2) >= 10(-15) cm(2)/W and negligible NL absorption coefficient were determined. The large values of the NL refractive index and the very small NL absorption indicate that these materials have large potential for all-optical switching applications. (C) 2009 American Institute of Physics. [doi: 10.1063/1.3212972]